Entity Framework Core in Action - Smith, Jon (Manning Publications, 2018)
Using crystal-clear explanations, real-world examples, and around 100 diagrams, Entity Framework Core in Action teaches you how to access and update relational data from .NET applications. You'll start with a clear breakdown of Entity Framework, long with the mental model behind ORM. Then you'll discover time-saving patterns and best practices for security, performance tuning, and even unit testing. As you go, you'll address common data access challenges and learn how to handle them with Entity Framework.
Keywords: Entity Framework (Software framework); Database design; Relational databases; Bases de données; Conception; Bases de données relationnelles